2022
DOI: 10.1021/acsami.2c06374
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Contact Electrification and Dynamic p–n Junction Modulation Effects in Triboelectrification

Abstract: The triboelectric effect occurs when two dissimilar materials are in physical contact, attributed to the combination of contact electrification (CE) and electrostatic induction. It has been extensively explored for the development of high-performance triboelectric nanogenerators (TENGs). In this paper, we report on, besides the CE-related charge generation, an additional charge generation phenomenon associated with the modulation of the p–n junction when two semiconductor materials [methylammonium lead iodide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The charge transfer process for the P–S TENG is similar to that of the S–S TENGs discussed in previous work. [ 39 ] When the separation distance of the friction materials is larger than L MAX ( d > L MAX > 0), negative and positive charges will stably accumulate on E#1 and E#2, respectively, owing to the ESI effect, as shown in Figure 4f. When the distance gets close to d < L MAX , the negative and positive charges on the surfaces of the friction materials shield each other.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The charge transfer process for the P–S TENG is similar to that of the S–S TENGs discussed in previous work. [ 39 ] When the separation distance of the friction materials is larger than L MAX ( d > L MAX > 0), negative and positive charges will stably accumulate on E#1 and E#2, respectively, owing to the ESI effect, as shown in Figure 4f. When the distance gets close to d < L MAX , the negative and positive charges on the surfaces of the friction materials shield each other.…”
Section: Resultsmentioning
confidence: 99%
“…This is estimated to be about 0.1–0.2 eV according to the I–V measurements in previous study. [ 39 ] The change of barrier height due to the contact–separation with polymer is much lower, at about 10–50 meV. The depletion width is given by xnormalp=2εrε0VDqNA$$\begin{eqnarray}{x}_{\rm{p}} = \sqrt {\frac{{2{\varepsilon }_{\rm{r}}{\varepsilon }_0{V}_{\rm{D}}}}{{q{N}_{\rm{A}}}}} \ \end{eqnarray}$$where ɛ r is the relative dielectric constant, ɛ 0 is the vacuum dielectric constant, V D is the barrier height, and N A is the carrier concentration of semiconductor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Varying composition ratio or percentage of metal ions of a perovskite could distinctly modify conductivity, electron affinity, piezoelectric property etc. These are anticipated to bring extra degrees of freedom to design new types of triboelectric nanogenerators and self-driven sensors, and they are very effective in altering material properties [251]. However, the lack of systematic investigation and fundamental research have inhibited its progress, and most of the research relied on the trial-and-error approach with no theoretical guidance for material and device development.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…At the first stage of the TVNG development, various conventional semiconductors, e.g., Si, [ 8b,c,9b,11 ] GaAs, [ 9d ] and GaN, [ 9b,c ] have been employed as the main frictional layer of the TVNG. The series of halide perovskite, e.g., methylammonium lead iodide (MAPI), [ 10 ] Cs 0.175 FA 0.750 MA 0.075 Pb(I 0.880 Br 0.120 ) 3 (CsFAMA), [ 12 ] and CsPBr 3 , [ 9a ] were then selected alternatively for the TVNG. Due to excellent optoelectronic performance of perovskite, experiments have confirmed that the tribovoltaic effect can work synergistically with the photovoltaic effect.…”
Section: Introductionmentioning
confidence: 99%